Treatment of water using Arc discharge plasma in Patan area - Shrestha, Rajesh; Joshi, Chet Raj; Subedi, Dipak Kumar; Pandey, Narayan; Bhattarai, Mohan Raj; Acharya, Rajan (Patan Prospective Journal, 2022)
The quality of drinking water has been degraded and declining day by day and its impact is directly seen on human health and other organisms too. So, the way we want to solve this problem by using new technology which was not based on the Plasma Treatment. Plasma based technology which is one of the best and new technology it takes a short time for improvement of water quality. Water sample collected from various sources within Patan from different sources such as Jar water, Ground water, Tap water and Stone spout water. The concentration of ammonia in the Jar and Tap water increased at 10 seconds after the sample was treated with Plasma. The hardness of groundwater increased significantly in all time periods as compared to without treatment. Overall, the hardness of Tap water decreased when treated with Plasma. But in case of Stone Spout water, hardness increased during 5 and 15 seconds whereas it decreased at 10 seconds. The concentration of Chloride only decreased in case of Jar water whereas there was a significant increase in its amount in all other remaining samples in each time factors i.e., 5,10,15 seconds. By using this technology water quality can be improved within short time.